Republic of Lebanon--Good Jobs Needed : The Role of Macro, Investment, Education, Labor and Social Protection Policies - World Bank (Washington, DC, 2013)
This report develops a strategy to support employment creation in Lebanon and improve labor market opportunities for its work force. The analysis is based on a new survey of the labor force and employers, and a General Equilibrium Model of the Lebanese economy, both developed in the context of this Technical Cooperation Program. The policy recommendations are the result of consultations with counterparts and different stakeholders. The report is organized in six chapters. Chapter 1 summarizes the main findings of the analysis and policy recommendations. Chapter 2 analyzes the main characteristics of the Lebanese labor market and identifies key issues that require attention. Chapter 3 focuses on ways to improve macroeconomic conditions and investment opportunities in order to enhance growth potential and promote the creation of high quality jobs. Chapter 4 discusses how current initiatives regarding active labor market programs (ALMPs) could be transformed into an integrated system of employment and training services that would be managed and monitored by the public employment agency (the National Employment Office) but implemented by private providers that would help individuals access jobs - whether wage or self-employment. Chapter 5 deals with the labor market distortions created by social insurance and regulations on types of contracts, dismissal procedures, and minimum wages. Finally, Chapter 6 analyses the potential impacts on labor market outcomes of alternative macroeconomic and social insurance policies based on the general equilibrium model.